The impact of early giftedness identification on long-term academic success: a cross-sectional study in King Abdullah II schools for excellence in Jordan - Shaheen, Hassan Rafi’ Ali (Frontiers in Education, 2025)
BackgroundEarly identification of gifted students plays a crucial role in shaping their academic success. However, the extent to which the age of gifted identification, participation in gifted programs, and socio-demographic factors influence academic performance remains inconclusive. This study investigates the relationship between these factors and academic success among students in King Abdullah II Schools for Excellence.MethodsA cross-sectional study was conducted with 250 gifted students selected through convenience sampling. Data were collected using a structured questionnaire assessing demographic characteristics, age of gifted identification, type and frequency of participation in gifted programs, and academic performance (GPA and standardized test scores). Descriptive statistics, independent t-tests, ANOVA, chi-square tests, and multiple regression analysis were used for data analysis in SPSS v.27, with a significance level of p < 0.05.ResultsThe findings revealed that gender was the only significant predictor of GPA, with male students (M = 86.94, SD = 8.55) outperforming female students (M = 84.03, SD = 8.41, F(1, 248) = 7.35, p = 0.0072). No significant differences were found in standardized test scores based on gender, school region, socioeconomic status, or grade level. Regression analysis showed that gifted identification age, type of gifted education received, and participation frequency in gifted programs were not significant predictors of academic success.ConclusionWhile gender differences in GPA were observed, other demographic factors and participation in gifted programs did not significantly influence academic performance. These findings suggest that the quality of gifted education programs and students’ self-regulation strategies may be more crucial than mere participation. Future research should focus on how instructional approaches and cognitive skills impact long-term academic outcomes.